The Country Boy: Investigating the Dennis Potter Archive, Forest of Dean, England. (13th April 2023) - Cook, John R.
This article presents scholarship relating to work conducted in the Dennis Potter Archive, Dean Heritage Centre, Dean Museum Trust, England. It argues that the Dennis Potter Archive is a significant archive consisting of handwritten manuscripts and notebook drafts of virtually all of the work of famed writer Dennis Potter (1935–94), allowing us unique access to the engine room of his creativity. The article focuses on the 'discovery' of Potter works previously unknown and/or inaccessible, including completed drafts of unproduced television plays and unproduced film screenplays. It also sheds new light on the genesis of perhaps Potter's most famous work, The Singing Detective (BBC TV 1986). It shows how this began as a 'last' television play, but that as it developed, Potter reached back to themes and preoccupations he first explored as a young man in an unpublished novel, written decades earlier. Marrying research in the archive with statements Potter gave about his work during his lifetime, the article uses accumulated Potter scholarship, together with manuscript critical analysis and dating, in order to piece together a clearer and fuller understanding of the working life of one of the most famous names in British television and film history.